SARS-CoV-2 UK, South African and Brazilian Variants in Karachi- Pakistan - Khan, Adnan; Hanif, Muhammad; Ahmed, Akhtar; Syed, Sarosh; Ghazali, Saqib; Khanani, Rafiq (Frontiers in Molecular Biosciences, 2021)
The COVID-19 pandemic has been evolving in Pakistan with the emergence of the United Kingdom, South African, and Brazilian variants. These variants of concern (VOC) are known for increased transmissibility and can also be responsible for avoiding immune responses. The gold standard to detect VOC is sequencing, however routine genomic surveillance in resource-limited countries like Pakistan is not always readily available. The inadvertent detection of the B.1.1.7 (United Kingdom) VOC by a target failure due to the key deletion in spike Δ69-70 by commercially available PCR assay helps to understand target failures as an alternative approach to detect variants. In pursuit of VOC it was further discovered that a deletion in the ORF1a gene (ORF1a Δ3675-3677) is common in B.1.1.7, B.1.351 (South African), and P.1 (Brazilian) VOC. The Real-Time Quantitative PCR (RT-qPCR) assay can distinguish target failures and can discriminate SARS-CoV-2 VOC. The study uses positive samples archived in respective labs. Samples were divided into two groups. Group I constitutes 261 positive samples out of total of 16,964 (1.53%) performed from August till September 2020, while group II consists of 3501 positive samples out of a total of 46,041 (7.60%) performed, from November 2020 till January 2021. The RT-qPCR analysis showed that no VOC was present in positive samples of group I. However, a staggering difference in results was noted in group II where the positivity ratio increased exponentially and the VOC started appearing in significant numbers (53.64%). This concludes that the third wave in Pakistan is due to the importation of SARS-CoV-2 variants.